On the Edge of War and Society: Canadian Pentecostal Bible School Students in the 1940s - Ambrose, Linda (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2013)
During World War II the Pentecostal Assemblies of Canada put forth arguments on behalf of bible college students concerning military service exemptions, chaplaincy appointments, and veterans’ benefits. The paper deals specifically with the Rev. J.E. Purdie, Principal of the Western Bible College in Winnipeg, his efforts on behalf of his students, and one particularly complex case where attempts were made to have the student exempted from serving, and failing that, to have him appointed as a military chaplain. After the young man’s premature release from service, Purdie argued that he should be entitled to veteran’s benefits to pay for his bible college training. What initially appeared as a bid to protect the individual rights of one young conscript was in fact part of a much larger effort as Pentecostals asserted their right (and by extension the right of other marginal religious groups) to be included in the broader liberal framework in Canada. This case study is significant because it addresses themes of public religion, specifically how Pentecostals challenged the ‘liberal order framework,’ by attempting to carve out recognition for themselves among the religious groups that were acknowledged as legitimate players in Canada’s public affairs.